"A Type of Student They Actually Want": Narratives from and about a Sixth-Grade Student with a Specific Learning Disability. Issue 1 (2nd January 2021) - Brodeur, Katherine
Abstract: This case study contrasts sixth-grade student Antonio's perspective of himself as a "good student" with perceptions some of Antonio's teachers held related to his classification as a student with a Specific Learning Disability and an English Learner as enacted in classroom literacy practices. With Antonio's voice at the center, multimodal narratives woven from interviews and observations focus on the moments of tension where Antonio was not recognized as the type of student he saw himself to be. Through analysis of these scenes, I question the usefulness of both his "good student" identity and school designations of disability and English proficiency for Antonio and students who may be labeled in similar ways by schools.